2005
DOI: 10.1111/j.1468-2982.2005.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation and Platelet-Leucocyte Interaction in Patients with Migraine. Subtype Differences and Influence of Triptans

Abstract: As migraine is the result of an inflammatory mechanism with serotonergic signalling, leucocyte function, platelet function and intercellular communication between those cells is likely to be connected to the final pathway of the disease. We examined P-selectin expression on platelets (platelet activation) and leucocyte-platelet aggregate formation in 72 migraine patients during their attack-free interval and controls using a flow cytometric assay. Patients suffering from migraine without aura had a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…Serotonin plays an important role in the pathogenesis of migraine, 90% of which is contained within platelets and it is released from the platelets depending on the demand (19). Zeller et al evaluated the P-selectin expression on platelets in patients with migraine and found an increase in platelet activation and leucocyte-platelet aggregation formation as compared to healthy controls, especially in migraine patients without auras (20). The levels of platelet activator factor, which play an important role in numerous inflammatory and thrombotic processes and serve as the mediator in phospholipid structure, was seen to increase in patients with migraine during attacks (21).…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin plays an important role in the pathogenesis of migraine, 90% of which is contained within platelets and it is released from the platelets depending on the demand (19). Zeller et al evaluated the P-selectin expression on platelets in patients with migraine and found an increase in platelet activation and leucocyte-platelet aggregation formation as compared to healthy controls, especially in migraine patients without auras (20). The levels of platelet activator factor, which play an important role in numerous inflammatory and thrombotic processes and serve as the mediator in phospholipid structure, was seen to increase in patients with migraine during attacks (21).…”
Section: Discussionmentioning
confidence: 99%
“…A biochemical theory of migraine implicates vasoactive substances in migraine, such as 5-hydroxytryptamine (serotonin), and there is evidence that serotonin metabolism is impaired in migraineurs (13) and that serotonin released from aggregating platelets may be involved in the vasoconstriction and vasodilation associated with migraine headache (MH) (14). In addition, research implicates altered platelet activity in migraine (1420). …”
Section: Introductionmentioning
confidence: 99%
“…Migraine [29] Platelet activation and leukocyte-platelet aggregation were significantly increased during migraine headaches in patients without aura vs. control volunteers in flow cytometry assays, but not in migraine patients with aura. All patients had an increased baseline level of platelet activation, and triptan drugs appeared to downregulate platelet aggregation.…”
Section: Heparin-induced Thrombocytopeniamentioning
confidence: 99%
“…Given the number and variety of bioactive substances secreted by platelets (Table 1), it is unsurprising that they have been implicated in the development or severity of an array of disorders (Table 2) [11,[24][25][26][27][28][29][30][31][32][33][34][35][36]. Some of these disorders may appear obvious (thrombosis and restenosis) but others may not (psoriasis and migraine).…”
Section: Disorders Involving Local and Systemic Platelet Activationmentioning
confidence: 99%